Set to its place: first DNA data on freshwater tardigrades of Sakhalin (Far East Russia) shed light on the phylogenetic position of Mixibius (Eutardigrada: Hypsibioidea) - Tumanov, Denis V. (Zootaxa, 2026)
In this paper I present the results of the first faunistic investigation of the Sakhalin freshwater tardigrade fauna with the use of the integrative taxonomy. In samples of bottom sediments collected in several rivers of South Sakhalin, I found eight species representing three of the four parachelan superfamilies. For most of the species, I obtained mitochondrial COI and nuclear ribosomal 18S rRNA, 28 rRNA and ITS-2 nucleotide sequences, as well as morphological data obtained using light contrast and scanning electron microscopy. The number of tardigrade species known for Sakhalin Island increased from 1 to 9. Among the eight species one is similar to Dactylobiotus dervizi, previously known from Komandorskiye Islands, and one—to Murrayon hastatus. The remaining six species, representing the genera Mixibius, Hypsibius, Dianea and Mesobiotus, are new for science, yet their formal description is not possible because of the small number of isolated specimens. Nevertheless, the inclusion of new molecular data in the phylogenetic analysis of the superfamily Hypsibioidea revealed, for the first time, the presence of a well-supported clade of the enigmatic genus Mixibius and allowed for a establishing its phylogenetic position as a sister clade to the genus Acutuncus within the family Acutuncidae. Moreover, a critical analysis of original descriptions of two species of the genus Mixibius, M. parvus and M. tibetanus, resulted in their transfer to the genus Isohypsibius on the basis of claw morphology. In consequence, amended diagnoses of the family Acutuncidae and the genus Acutuncus are given.